2006
DOI: 10.1111/j.1442-2042.2006.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral testicular metastases from prostatic carcinoma

Abstract: Testicular metastasis from carcinoma of the prostate is rare. We report a case of carcinoma of the prostate with bilateral testicular metastases 7 years after the initial diagnosis. The exact prognosis is not known but it usually indicates advanced disease. Although testicular metastasis is uncommon, it should be considered when a patient presents with a lump in the testis, particularly in a patient known to have another primary malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 3 publications
1
20
0
2
Order By: Relevance
“…In 15% of cases, both testicles are affected [ 6 ]. The patient is typically asymptomatic, and the metastasis is often discovered incidentally after therapeutic orchiectomies or during autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…In 15% of cases, both testicles are affected [ 6 ]. The patient is typically asymptomatic, and the metastasis is often discovered incidentally after therapeutic orchiectomies or during autopsies.…”
Section: Discussionmentioning
confidence: 99%
“…For the cases with metastasis to the testis detected long after initiation of treatment for the prostate cancer, androgen deprivation had been continued even though they had the potential to be aggressive [5]. Manikandan et al had improved survival (four years at time of their report) in their case with the patient receiving 8 cycles of chemotherapy followed by atrasentan 10 mg/day [8]. The use of multimodal therapy in our patient presenting with testicular metastasis without prior treatment for his prostate cancer led to an improved survival of two years as against a survival of less than one year observed in other cases/ series [2].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these are diagnosed on routine histopathological examination of testicular tissue removed for the treatment of prostate carcinoma. 3,6,8,9,12,14,15 Manikandan 2006 et al reported a case of bilateral testicular metastasis 7 years after the initial diagnosis of prostate carcinoma where the patient presented with testicular lump. 9 We report this rare case of bilateral testicular metastasis from prostate carcinoma in orchiectomy specimen done for the treatment of prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,5,6 Testicular metastasis from PC are rare despite the proximity. 3,4,6,7,8,9,10 We report a rare case of bilateral testicular metastasis in orchiectomy specimen done for treatment of PC.…”
Section: Introductionmentioning
confidence: 98%